Anisotropic lithium-ion insertion into silicon anodes: Microscopic analysis of structural changes and composition gradients - Norihiro Shimoi; Tatsuyuki Sato; Masae Komatsu (Heliyon)
In this study, we investigated the process of lithium-ion insertion into silicon anodes for lithium-ion batteries using inductively coupled plasma treatment. We observed a distinctive stripe-like pattern on the silicon substrate surface after lithium-ion insertion. Cross-sectional analysis using various microscopy techniques revealed that these stripes corresponded to amorphous with higher lithium content, whereas the surrounding areas retained the crystalline silicon structure with lower lithium content. The study showed that lithium preferentially enters the silicon crystal along certain crystallographic planes, particularly the (111) and (002) planes. The boundaries between lithiated (amorphous) and non lithiated (crystalline) regions showed a terrace-like pattern along these planes. Electron energy loss spectroscopy analysis confirmed a higher lithium content in the amorphous stripe regions, than in the surrounding crystalline regions. The lithium-to-silicon ratio in the amorphous regions was estimated to be about 20:80 atomic percent, whereas in the crystalline regions, it was about 6:94 to 9:91 atomic percent. The research findings provide insights into the anisotropic nature of lithium-ion insertion into silicon and shows how the process leads to localized amorphization and structural changes. These findings contribute to the understanding of silicon anode behaviour in lithium-ion batteries and may support future designs for improved performance and longevity.